Penggunaan Shuujoshi Kana dan Na oleh Tokoh Midoriya dalam Anime Boku No Hero Academia Dai San Ki (Kajian Sosiolinguistik) - Nur Romadloniyah; Didik Nurhadi (Universitas Muhammadiyah Prof. Dr. Hamka, 2021)
In Japan, the use of a male and female language are still regularly used by Japanese society itself. The use of a male and female language in Japanese society is caused not as it were by contrasts in gender or social status, but too impacted by the concepts of ‘insider’ (uchi) and ‘outsider’ (soto) which are connected to distinguish the scope of Japanese society itself. One of the characteristics of recognising the difference between a male and female language is the use of the final particle (shuujoshi) at the conclusion of sentence. Shuujoshi is used by speakers to specific the emotions they need to convey to listeners. This research examines three issues, 1) which word classes are taken after by shuujoshi kana and na, 2) how to use shuujoshi kana and na, 3) what social factors impact the use of shuujoshi by Midoriya within the anime Boku no Hero Academia Dai San Ki. To answer the first issues, Sudjianto and Dahidi’s (2012) theory is used, for the second problem, Chino’s (2008) theory is used, meanwhile the third problem uses Chaer and Agustina’s (2004) theory. The results of the first problem show that shuujoshi kana by Midoriya in anime Boku no Hero Academia Dai San Ki follows doushi, keiyoushi, meishi, fukushi, jodoushi, and joshi, and for shuujoshi na follows doushi, keiyoushi, meishi, jodoushi, and joshi. Furthermore, the use of shuujoshi kana by Midoriya in anime Boku no Hero Academia Dai San Ki was found with results, showing uncertainty: “I wonder” with the amount of data as much as 8, showing question to someone: “I wonder” with the amount of data as much as 4, and showing indirect hopes or wishes: “I wonder” with the amount of data as much as 4, while the use of shuujoshi na by Midoriya in anime Boku no Hero Academia Dai San Ki was found with results, showing a sense with the amount of data as much as 4, asking others to agree with the amount of data as much as 4, refine the impact of an confirmation with the amount of data as much as 5, and showing the prohibition with the amount of data as much as 6. Then the social factors that impact the use of shuujoshi kana and na by Midoriya in anime Boku no Hero Academia Dai San Ki are: 1) the speaker’s social character, to be specific Midoriya is the student of the U.A. Academy (1-A), 2) the listener’s social identity, namely Midoriya’s classmate, Midoriya’s close friend, and criminals, 3) the environment where the discourse occasion took put, specifically U.A. Academy, U.A. Academy’s residence, the forest training camp, and the exam location.